Celluloid homes reading urban domestic spaces in four Filipino films - Quiling, Tito Ramos Jr. 1990-
"The house is debatably the most familiar and evocative form of space. Using domestic spaces as a link between cinema and architecture, this study examines four Philippine houses, periodicized in their social orientation, and reads the structures via phenomenology in architecture and of film. The discussions anchor on the architectural principles of Gaston Bachelard and Juhani Pallasmaa, while the filmic interpretation leans on the premises of Vivian Sobchack and Laura Marks. This research augments the exchange of meanings between man and space by analyzing the influence of specific domestic spaces. The selected films have visible architectural spaces, noting their various locations in the urban landscape, including certain fixtures and characteristics of domestic spaces that become significant in the experience of home. The four (4) films were produced and released from 1965-1985, in line with the Marcos Era. The domestic spaces in the study include the following: the bahay na bata in A Portrait of the Artist as Filipino (1965) by Lamberto Avellana, the shanty in "Hellow, Soldier", which is the second episode in Lino Brocka's Tatlo, Dalawa, Isa (1975), the one-and-a-half story house in Kisapmata (1981) by Mike De Leon, and the accesoria in Scorpio Nights (1985) by Peque Gallaga."